Hybrid nanoparticles obtained from mixed mesoglobules. (26th June 2015) - Trzebicka, Barbara; Haladjova, Emi; Otulakowski, Łukasz; Oleszko, Natalia; Wałach, Wojciech; Libera, Marcin; Rangelov, Stanislav; Dworak, Andrzej
Abstract: This article describes the preparation and characterization of mixed mesoglobules from two thermoresponsive polymers: poly(N-isopropyl acrylamide) (PNIPAM) and poly(2-isopropyl-2-oxazoline) (PIPOX) and their coating with a crosslinked shell to obtain hybrid nanoparticles. The variations in dimensions and stability of the mixed mesoglobules prepared with different compositions (20/80, 50/50 and 80/20 PIPOX-to-PNIPAM weight ratios) and using different heating protocols (gradual and abrupt heating) indicate their sensitivity to both parameters. Unlike neat PIPOX particles as well as PIPOX-rich ones, the mixed particles with higher PNIPAM content (20/80 and 50/50) exhibit a fully reversible coil-to-globule phase transition implying that in these cases PNIPAM effectively prevents the crystallization of PIPOX. The mesoglobules were covered with a cross-linked polymeric shell by seeded radical copolymerization of NIPAM and N, N-methylenbisacrylamide. The resulting hybrid nanoparticles retain their stability and do not disintegrate at low temperatures. Graphical abstract: Highlights: Mixed mesoglobules from PNIPAM and PIPOX were prepared. PNIPAM effectively prevents the crystallization of PIPOX in mesoglobules. Heating protocol significantly influences the morphology of mesoglobules. Nanoparticles were obtained by covering the mesoglobules with cross-linked shell. Hybrid thermoresponsive nanoparticles exhibit good colloidal stability.